Reformulation and Appropriation of Traditional Knowledge in Industrial Ayurveda: The Trajectory of Jeevani. Issue 4 (1st December 2020) - Madhavan, Harilal; Gaudillière, Jean-Paul
Abstract: In India, the industrial sector that specializes in the invention, production, and marketing of neotraditional therapeutic specialties has been rapidly growing for two decades. In addition to standard pharmaceutical laboratory knowledge, it heavily mobilizes local medical knowledge. This article follows the trajectory of a new formulation called Jeevani, originating in the mining of both the classical Ayurveda texts and the tribal healing practices in the Indian state of Kerala. We investigate the strong coupling established by the reformulation regime between the invention of complex polyherbal therapeutic preparations with local forms of appropriation, namely Indian patents and benefit-sharing agreements.